Engineering the moss Physcomitrium patens to produce proteins with paucimannosidic glycans - Jonner, Jessica; Fode, Benjamin; Koch, Jonas; Boller, Sören; Dabrowska-Schlepp, Paulina; Schaaf, Andreas; Sievert, Christian (Frontiers in Plant Science, 2025)
The moss Physcomitrium patens is an advantageous host for the production of biopharmaceutical proteins, particularly due to the ease of glyco-engineering. However, the ability to produce proteins with paucimannosidic (MM) glycans in this species currently depends solely on the nature of the product. MM glycans offer benefits for some therapeutic proteins by facilitating their import into target cells via a presumed mannose receptor. Here, we describe the use of Spodoptera frugiperda enzymes expressed in moss to produce recombinant human lysosomal acid α-glucosidase with mainly MM glycans. We tested the expression of mannosidase type III and a hexosaminidase by varying the promoter strength and protein localization. The parental line produced recombinant α-glucosidase with no detectable MM glycans at all, whereas the weak expression of mannosidase type III targeted to the medial Golgi produced 4% MM glycans. The strong expression of a hexosaminidase targeted to the extracellular space increased the MM glycan content to 43.5%. Unlike previous attempts to express proteins with MM glycans in plants, neither of our introduced modifications interfered with growth or recombinant protein production. Our data confirm that the finely tuned expression and cellular localization of the glycosylation machinery can improve the efficiency of glyco-engineering. We also exploit the assembly of DNA fragments in vivo, which overcomes the limitations of traditional knock-in methods and facilitates the screening of different genetic elements. Our combined methods therefore represent the first straightforward approach allowing the production of recombinant proteins with abundant MM glycans.